Obstructive sleep apnea and structural/functional properties of the thoracic ascending aorta: The Multi-Ethnic Study of Atherosclerosis (MESA) - Kwon, Younghoon (Cardiology, 2019)
BACKGROUND: Structural and functional properties of the proximal thoracic aorta have important implications in clinical and subclinical cardiovascular disease (CVD). We examined whether obstructive sleep apnea (OSA) is associated with proximal aortic size and aortic stiffness in a multi-ethnic community-based cohort. METHODS: The sample included the Multi-Ethnic Study of Atherosclerosis (MESA) Sleep Ancillary study participants without known CVD who underwent cardiac magnetic resonance imaging. The main exposure variable was OSA severity based on polysomnography-derived apnea hypopnea index (AHI) (normal [AHI <5/hr]; mild [5≤AHI<15]; moderate to severe [AHI ≥15]). Study outcomes were ascending aortic diameter (AoD [cm]), aortic pulse wave velocity (AoPWV [m/sec]) and ascending aortic distensibility (AAD [%/mmHg]). Analyses were performed in the overall sample and in sex-specific strata, adjusted for multiple potential confounders. RESULTS: The 708 participants were 55.9% female and on average 68 years old [54–93 years]. There was a significant trend (p<0.0001) of greater mean [SD] AoD across the three OSA groups: normal (n=87) = 3.13 cm [0.35]; mild (n=215) = 3.25 [0.34]; moderate to severe (n=406) = 3.37 [0.36]). In adjusted analysis, participants with moderate to severe OSA had greater mean AoD compared with the normal group: adjusted mean difference [95% CI] = 0.12 cm [0.05, 0.20], p= 0.002. This AoD gradient was observed in women but not in men (p for interaction=0.02). No differences were found in AoPWV or AAD among OSA groups. CONCLUSION: In a diverse community-based cohort, moderate to severe OSA (vs. no OSA) was associated with larger ascending aortic diameter in women.